Caspofungin enhances the potency of rifampin against Gram-negative bacteria - Li, Haotian; Zhu, Xiaojing; Zhang, Xing; Dong, Changjiang (Frontiers in Microbiology, 2024)
Developing antibiotic adjuvants is an effective strategy to combat antimicrobial resistance (AMR). The envelope of Gram-negative bacteria (GNB) is a barrier to prevent the entry of antibiotics, making it an attractive target for novel antibiotic and adjuvant development. Here, we identified an FDA-approved Caspofungin acetate (CAS) as an antibiotic adjuvant against GNB, which could enhance the antimicrobial activity of rifampin or colistin against various GNB strains in vitro, Moreover, Galleria mellonella larvae infection model also indicated that CAS significantly potentiated the efficacy of rifampin against multidrug-resistant E. coli 72 strain in vivo. Most importantly, CAS was less susceptible to accelerating the resistance development of drug-sensitive strain E. coli MG1655. Functional studies and RNA-seq analysis confirmed that the mechanisms by which CAS enhanced the antimicrobial activities of antibiotics were involved in permeabilizing the bacterial cell envelope, disrupting proton motive force and inhibiting bacterial biofilm formation. Additionally, it has been found that PgaC is the CAS target and enzymatic assay has confirmed the inhibition activity. Collectively, our results illustrate the feasibility of CAS as an antibiotic adjuvant against GNB, which is an alternative strategy of anti-infection.